FEASIBILITY AND DOSIMETRIC EVALUATION OF CT-BASED HIGH DOSE-RATE INTERSTITIAL BRACHYTHERAPY IN LOCALLY ADVANCED CERVICAL CANCER: A PROSPECTIVE STUDY - Dr Aruna R.; Dr Thejaswini B; Dr G V Giri; Dr Aradhana Katke; Dr Nanda R; Dr Shwetha (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Purpose: This study evaluates the feasibility and efficacy of CT-based high dose-rate interstitial brachytherapy (HDR-ISBT) for the treatment of locally advanced uterine cervical cancer, following GEC-ESTRO guidelines. The primary objectives were to assess dosimetric outcomes, evaluate organ-at-risk (OAR) toxicity, and analyze local control and survival rates. Methods and Materials: A cohort of 20 patients with biopsy-confirmed FIGO stage IIB-IIIB cervical cancer was treated using HDR-ISBT with the Syed-Neblett template, following external beam radiotherapy (EBRT) of 45 Gy in 25 fractions. Treatment planning was conducted with CT-based imaging, and dose-volume histograms (DVH) were generated for the high-risk clinical target volume (HR-CTV), intermediate-risk clinical target volume (IR-CTV), and OARs (bladder and rectum). The biologically equivalent dose in 2-Gy fractions (EQD2) was calculated for comparison. Results: The median D90 for HR-CTV was 6.09 Gy per fraction (range: 3.57–6.81 Gy), and for IR-CTV, it was 4.35 Gy (range: 1.92–5.29 Gy). The median V100 for HR-CTV was 90.82% (range: 67–97%), and for IR-CTV, it was 54% (range: 40–73.9%). After adding the EBRT dose, the median EQD2 D90 for HR-CTV was 66.65 Gy, and the D100 was 53.45 Gy. The D2cc doses to the bladder and rectum were 66.5 Gy (range: 56.8–78.4 Gy) and 67.9 Gy (range: 61.7–73.9 Gy), respectively. Conclusion: CT-based HDR-ISBT is a feasible and effective approach for treating locally advanced cervical cancer, providing adequate target volume coverage and minimizing OAR exposure. While CT is appropriate for OAR delineation, MRI remains the preferred modality for precise tumor volume contouring.